Prenatal Diagnosis and Postnatal Ultrasound Findings of Cloacal Anomaly: A Case Report. (4th October 2012) - Rios, Lívia Teresa Moreira; Araujo Júnior, Edward; Nardozza, Luciano Marcondes Machado; Caetano, Ana Carolina Rabachini; Moron, Antonio Fernandes; Martins, Marília da Glória
Abstract : Cloacal malformation is an extremely rare fetal pathological condition that presents as a variety of defects. It predominantly affects females, with prevalence of 1 in 50, 000 births. Prenatal ultrasonography on a 20-year-old caucasian woman (G4P1A2) at 33 weeks of pregnancy showed the fetus having a large cystic mass in the lower abdomen with a single septum, bilateral hydronephrosis, ambiguous genitalia, and a single umbilical artery. The pregnancy developed accentuated oligohydramnios, and presence of a fetal brain-sparing effect was diagnosed using arterial Doppler velocimetry. The newborn showed abdominal distension, ambiguous genitalia, and rectal atresia, with a single perineal opening. Pelvic ultrasound done on the first day after delivery revealed the presence of a large retrovesical septated cystic mass of dense content in the fetal abdomen, and bilateral hydronephrosis. Hysterotomy was performed, and 70 mL of dense liquid was drained through an abdominal colostomy. The infant died on the 27th day of life as a result of infectious complications. Prenatal diagnosing of female urogenital anomalies is usually difficult because of their rarity, different types of manifestation, and lack of characteristic ultrasound signs. Presence of a septated cyst with dense content in the fetal abdomen confirms the finding of hydrometrocolpos, thus raising clinical suspicion of a cloacal anomaly.